Pengaruh Akupresure Pada Titik Perikardium 6 Terhadap Intensitas Mual Muntah Pada Ibu Hamil Trimester I di TPMB I Tahun 2023 - Iis Ismawati; Dewita Rahmatul Amin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Nausea and vomiting in pregnancy occur as a result of changes in the endocrine system that occur during pregnancy. According to WHO, pregnancies with excessive nausea and vomiting reach 12.5% of all pregnancies in the world with varying incidence rates. In Bekasi Regency in 2018 there were 206 pregnant women with nausea and vomiting in the first trimester. Therapy to reduce nausea and vomiting can be done by means of acupressure at pericardium point 6 3 times a day with a minimum duration of 10 minutes. The aim of this study was to determine the effect of acupressure at pericardium point 6 on the intensity of nausea and vomiting in pregnant women at TPMB I in 2023.The research method used is the Pre-experimental One Group With Pre-Post Test Design method. Sampling was taken with a total sampling of 30 people. Data analysis used frequency distribution and Wilcoxon test. This research uses primary data from observation values by researchers.The results of the study showed that all respondents experienced a decrease in nausea and vomiting after acupressure was carried out at point P6. The P value is 0.000 < 0.05 so it can be concluded that Ha is accepted or Ho is rejected, meaning there is a significant influence on administering acupressure at point P6 to pregnant women with nausea and vomiting at TPMB I in 2023.It is hoped that this research can be used as an alternative non-pharmacological technique that is easy to carry out without harmful effects in providing intervention for cases of nausea and vomiting in pregnant women.